Evaluasi Kinerja Karyawan Wisata Alama Gosari (Wagos) Menggunakan Pendekatan Balanced Scorecard: Analisis Empat Perspektif Untuk Peningkatan Data Saing Pariwisata Berkelanjutan - Chrisananda, Riska Anin; Jitmau, Yuzak; Dwiningwarni, Sayekti Suindyah (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2026)
This study aims to evaluate employee performance at Wisata Alam Gosari (WAGOS) using the Balanced Scorecard approach. This approach provides a comprehensive overview of organizational performance through four perspectives: financial, customer, internal business processes, and learning and growth. The research method employed is qualitative descriptive, with data collected through observation, interviews, and documentation. The results indicate that overall employee performance at WAGOS is satisfactory, particularly in visitor satisfaction and internal process effectiveness. However, improvements are still needed in providing safety and health equipment for visitors, as well as training programs to enhance employee professionalism. This study is expected to serve as a reference for other tourism managers in conducting comprehensive and sustainable performance evaluations